Variable duty cycle heating strategy based online two-dimensional model for self-heating lithium-ion battery. (15th November 2022) - Lin, Cheng; Tao, Zhenyi; Tian, Yu
Abstract: It is a challenge to online obtain the time-varying temperature distribution of self-heating lithium-ion battery (SHLB), which results in a lack of theoretical basis for heating strategies to optimize heating time and temperature distribution uniformity. To reveal the evolution of temperature distribution and improve the temperature distribution uniformity of SHLB during heating, a variable duty cycle heating strategy with online two-dimensional model is proposed. Distributed thermal equivalent circuit model coupled with electrical model can obtain the two-dimensional temperature distribution of battery in real-time. The results show that the maximum temperature gap between the proposed model and the finite element model (FEM) is only 1.2 °C, while 90 % of the calculation time is saved. The proposed model can calculate the temperature distribution almost as accurately as FEM under different conditions. Based on the proposed model, heating currents of different values and duty cycles are applied to investigate their effects on the temperature distribution evolution of SHLB. Finally, we propose a variable duty cycle heating strategy that can automatically switch the duty cycle of the heating current according to the heating uniformity requirements in order to consider both heating time and the temperature distribution uniformity. The results show that compared with constant duty cycle heating, the variable duty cycle heating strategy can reduce the temperature difference by 35 % and limit the temperature difference to the pre-set boundary. The proposed strategy and method have considerable potential for use as improved temperature uniformity in battery management system. Graphical abstract: Unlabelled Image Highlights: An online two-dimensional model for self-heating lithium-ion battery High accuracy but reduced complexity compared to finite element model The effect of current on the temperature distribution evolution is explored. A variable duty cycle heating strategy to improve temperature uniformity significantly with less influence of heating time